Juvenile Gangrenous Vasculitis of the Scrotum - Cameron S. Nichols; Fnu Nutan (Internal Medicine, 2021)
A 17-year-old healthy male presented to the emergency room with painful black ulcers on his scrotum that developed acutely over 24-hours. Other symptoms included fatigue, nausea, and vomiting. He had a mild leukocytosis, but was afebrile.